2021
DOI: 10.3390/robotics10030107
|View full text |Cite
|
Sign up to set email alerts
|

Nut Unfastening by Robotic Surface Exploration

Abstract: In this paper, we present a novel concept and primary investigations regarding automated unfastening of hexagonal nuts by means of surface exploration with a compliant robot. In contrast to the conventional industrial approaches that rely on custom-designed motorised tools and mechanical tool changers, we propose to use robot fingers to position, grasp and unfasten unknown random-sized hexagonal nuts, which are arbitrarily positioned in the robot’s task space. Inspired by how visually impaired people handle un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The developed framework is a proof of concept tested in a simulation environment, and it proposed a trajectory-independent robotic path following for cutting, where the properties of the environment are uncertain. In another work, Rastegarpanah et al proposed a tactile based method for nut unfastening and this method was validated by unfastening the nuts of a Nissan Leaf LIB module [92]. The authors recognized unfastening as a main task in disassembly and showed the generalizability of the proposed method for unfastening the nuts in different sizes and shapes.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…The developed framework is a proof of concept tested in a simulation environment, and it proposed a trajectory-independent robotic path following for cutting, where the properties of the environment are uncertain. In another work, Rastegarpanah et al proposed a tactile based method for nut unfastening and this method was validated by unfastening the nuts of a Nissan Leaf LIB module [92]. The authors recognized unfastening as a main task in disassembly and showed the generalizability of the proposed method for unfastening the nuts in different sizes and shapes.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…[52] Some reviews provide a summary of disassembly approaches and related analysis of automation assessments for disassembly operations of spent LIBs, which can increase the circularity during the recycling and stress the necessity of technical developments in robotic disassembly. [53][54][55] After that, nearly all Li-ion batteries today are recycled through a process called "shredding," where the obtained components are shredded into very small pieces. [49,56] These shredding methods, involving multi-stage crushing, air classification, and fine screening, will produce a tremendous amount of impurities that are hard to separate in the subsequent process.…”
Section: Purity Of Recycled Cathode Materialsmentioning
confidence: 99%
“…Unscrewing is achieved with the help of a standard Cartesian impedance control scheme in combination with a custom nut-runner, which encloses the hexagonal-shaped screw head. Another unscrewing strategy for screws with a hexagonal shaped screw head was proposed in [13], where screw location and orientation are detected and the unscrewing makes use of a standard Cartesian impedance controller and a conventional 2-fingers gripper. In [14], an unscrewing robotic system for the automatic disassembly of electronic devices was developed.…”
Section: Introductionmentioning
confidence: 99%